1989
DOI: 10.1182/blood.v73.6.1699.bloodjournal7361699
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpromazine inhibits vesiculation, alters phosphoinositide turnover and changes deformability of ATP-depleted RBCs

Abstract: To delineate further the underlying mechanism by which amphiphilic drugs can modulate vesicle release from human RBCs, we studied the effect of chlorpromazine on erythrocyte vesiculation induced by ATP depletion. This was correlated with turnover of the phosphoinositides as well as RBC deformability during the process since phosphoinositide metabolism may be involved in shape regulation of RBCs. Echinocytic shape transformation and subsequent vesiculation of RBCs, which commonly occur during ATP depletion, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…Immediately before the start of the investigations, the cells were washed carefully in Dulbecco's PBS (9.6 g/l, Sigma) containing 0.1% glucose adjusted to pH 7. 4 (22). At concentrations below 200 µM, it does not significantly affect the osmolarity or the pH of a PBS (22).…”
Section: Drugs and Materialsmentioning
confidence: 99%
See 4 more Smart Citations
“…Immediately before the start of the investigations, the cells were washed carefully in Dulbecco's PBS (9.6 g/l, Sigma) containing 0.1% glucose adjusted to pH 7. 4 (22). At concentrations below 200 µM, it does not significantly affect the osmolarity or the pH of a PBS (22).…”
Section: Drugs and Materialsmentioning
confidence: 99%
“…RECENT EVIDENCE INDICATES that endothelial cell plasma membrane vesiculation in the form of caveolae serves as a membrane reservoir during stretch of the endothelial cells and possibly for transendothelial transport in certain domains of the cytoplasm (16,24,26). Previous studies have shown that the amphipathic, cationic, and antipsychotic drug chlorpromazine (CP) modulates the phospholipid bilayer balance by intercalation into the inner leaflet of the red blood cell plasma membrane (4). The drug may reach both sides of the membrane because it can cross the membrane, but, thereafter, CP selectively inserts into the inner half of the membrane bilayer by virtue of its cationic properties (1,4).…”
mentioning
confidence: 99%
See 3 more Smart Citations